2017
DOI: 10.1371/journal.pone.0183867
|View full text |Cite
|
Sign up to set email alerts
|

Catalase activity of IgG antibodies from the sera of healthy donors and patients with schizophrenia

Abstract: We present first evidence showing that some electrophoretically homogeneous IgGs from the sera of patients with schizophrenia (36.4%) and their Fab and F(ab)2 fragments as well as from healthy donors (33.3%) possess catalase activity. The relative catalase activity of IgGs from the sera of individual schizophrenia patients (and healthy donors) significantly varied from patient to patient, but the activity of IgGs from healthy donors is on average 15.8-fold lower than that for schizophrenia patients. After exte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 73 publications
(114 reference statements)
1
29
0
3
Order By: Relevance
“…In this work, we discovered antibodies hydrolyzing histones from the serum of patients with schizophrenia and described their biochemical properties. Earlier, we developed a method protocol for the isolation of electrophoretically homogeneous antibodies from different biological fluids that do not contain impurities of any canonical enzymes, which was used in numerous studies [ 17 , 30 , 31 , 32 , 33 , 34 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 47 , 48 , 50 ]. Fourteen previously proposed strict criteria were used to show that antibodies obtained using this method [ 26 , 30 , 31 , 32 , 33 , 34 ] do not contain impurities of any classical enzymes [ 30 , 31 , 32 , 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this work, we discovered antibodies hydrolyzing histones from the serum of patients with schizophrenia and described their biochemical properties. Earlier, we developed a method protocol for the isolation of electrophoretically homogeneous antibodies from different biological fluids that do not contain impurities of any canonical enzymes, which was used in numerous studies [ 17 , 30 , 31 , 32 , 33 , 34 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 47 , 48 , 50 ]. Fourteen previously proposed strict criteria were used to show that antibodies obtained using this method [ 26 , 30 , 31 , 32 , 33 , 34 ] do not contain impurities of any classical enzymes [ 30 , 31 , 32 , 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that some electrophoretically homogeneous IgGs (and their F(ab) and F(ab) 2 fragments) from the sera of patients with SCZ (36.4%) and from healthy donors (33.3%) possess catalase activity [122]. As in the case of the abzymes described above, it was shown that the catalase activity of all IgGs is their intrinsic property (Figure 10).…”
Section: Abzymes With Oxidation-reduction Activitiesmentioning
confidence: 80%
“…The K m and V max values were estimated using the nonlinear regression method in the Origin Pro v.8.6 program and were presented as linear transformations using a Lineweaver-Burk plot [54]. The value of K cat was determined by the formula K cat = V max /½AB, where [AB] is the total concentration of IgGs in the reaction mixture [40,42,49]. Errors in the values were within 7-15%.…”
Section: Silver Staining Methodmentioning
confidence: 99%
“…Ikhmyangan et al showed that polyclonal Abs from the sera of Wistar rats possess oxidoreductase activity in the presence and absence of hydrogen hydroperoxide [37][38][39]. In addition, our recent studies conducted together with the Institute of Chemical Biology and Fundamental Medicine (Novosibirsk, Russia) have reported catalase (CAT) activity in IgGs of patients with schizophrenia [40]. The study of the oxidoreductase activity of IgGs has not previously been conducted in patients with MS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation